PELATIHAN DIGITAL MARKETING PRODUK DI YAYASAN TUNAS ALAM MULIA BANTARGEBANG BEKASI - Djihadul Mubarok (Institut Bisnis Muhammadiyah Bekasi, 2021)
Tunas Alam Mulia Foundation which is located in Bantargebang Bekasi is one of the foundations that have a household business. From this household business, it is hoped that it can support the daily needs of the residents of the foundation. Several household businesses have been endeavored by the Tunas Alam Mulia Foundation. However, in the efforts that have been done, there were several obstacles faced, one of which is marketing. This year's PKM (Pengabdian Kepada Masyarakat) activities were designed and implemented by IBM (Institut Muhammadiyah Bekasi) Bekasi at the Alam Tunas Mulia Foundation to take the idea and initiate Digital Marketing Product Training activities to provide solutions to the obstacles faced by the Tunas Alam Mulia Foundation. This training was attended by selected 15 students of the Tunas Alam Mulia Foundation. This activity is carried out with the presentation method of providing material on Digital Marketing Products and marketing practices via social media and the internet.